The role of digital influencers on consumers' purchase intention in fashion - Gomes, Marina Alexandra Silva (2020)
In this digital Era, there has been an increasing interest in digital influencers, who convey their opinions to followers regarding brands and products. Considering that research on digital influencers’ role in marketing strategies is scarce, this study aims at assessing the role of digital influencers on purchase intention in fashion. The literature review allowed to identify key variables associated with digital influencers. A combination of methods was selected. Interviews with digital influencers were accomplished in order to deeply understand their perspectives. An online questionnaire addressing consumers who follow fashion digital influencers was conducted in order to test six hypotheses, which were proposed based on the literature review. A total of 345 responses was obtained. The quantitative data was analysed through IBM SPSS. Results indicate that, amongst the considered digital influencers’ characteristics, parasocial interaction and content quality positively influence purchase intention in fashion. Moreover, consumers’ attitude towards sponsored posts positively impacts purchase intention and it was demonstrated that this variable contributed the most to explain purchase intention of a recommended product. Regarding the interviewees’ opinion, the most important characteristics to achieve effectiveness are the connection and interaction with their followers, transparency, consistency and creativity demonstrated by digital influencers. This study highlights the digital influencers’ characteristics, which enhance their role on purchase intention, thus enriching the research on this theme and providing further investigation recommendations. It can also help fashion brands to better define social media strategies, when collaborating with digital influencers.